2019
DOI: 10.3390/cells8080848
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Agrin and RhoA Pathways Ameliorates Movement Defects and Synapse Morphology in MYO9A-Depleted Zebrafish

Abstract: Congenital myasthenic syndromes (CMS) are a group of rare, inherited disorders characterised by impaired function of the neuromuscular junction (NMJ). This is due to defects in one of the many proteins associated with the NMJ. In three patients with CMS, missense mutations in a gene encoding an unconventional myosin protein, MYO9A, were identified as likely causing their disorder. Preliminary studies revealed a potential involvement of the RhoA/ROCK pathway and of a key NMJ protein, agrin, in the pathophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Although it has been confirmed that agrin has an organizing role in synapse formation and stabilization in neuromuscular junctions, the effect of agrin on the repair of the central nervous system injury is unclear and seldom studied. 39-42 In the present study, we observed that recovery of function improved by exercise was accompanied by an upregulated expression of agrin in a rat model of stroke, and we confirmed that overexpressed agrin promoted synaptogenesis in cultured OGD neurons. Moreover, agrin contributed to the reconstruction of the neurovascular unit and improved the microenvironment of nerve regenerative niche by stabilizing the adherens junction proteins in brain endothelial cells.…”
Section: Discussionsupporting
confidence: 80%
“…Although it has been confirmed that agrin has an organizing role in synapse formation and stabilization in neuromuscular junctions, the effect of agrin on the repair of the central nervous system injury is unclear and seldom studied. 39-42 In the present study, we observed that recovery of function improved by exercise was accompanied by an upregulated expression of agrin in a rat model of stroke, and we confirmed that overexpressed agrin promoted synaptogenesis in cultured OGD neurons. Moreover, agrin contributed to the reconstruction of the neurovascular unit and improved the microenvironment of nerve regenerative niche by stabilizing the adherens junction proteins in brain endothelial cells.…”
Section: Discussionsupporting
confidence: 80%
“…Disruptions in the establishment of synapses is associated with morphological, cognitive and psychiatric disorders, but the precise mechanisms underlying these disorders remain unknown [42]. Changes in synapse structure and function are related to paralysis and muscular atrophy in amyotrophic lateral sclerosis (ALS) [43,44], impairment of the neuromuscular junction function and therefore, motor decline [45] or social and cognitive behaviors related to autism [46]. Thus the study of relevant mechanisms for synapse formation during development is a need.…”
Section: Discussionmentioning
confidence: 99%
“…Transient dual knockdown of egfra and erbb2 was induced using a Cas9 nuclease (New England Biolabs) in combination with transactivating RNA (tracr) and synthetic guide RNAs specific to zebrafish egfra and erbb2 genes (Merck). The non-targetting control in these experiments was a guide RNA targetted towards tyrosinase , a gene involved in pigment formation and therefore easy to identify when mutated, and which is used by others in the field as a CRISPR/Cas9 control (O’Connor et al, 2019; Varshney et al, 2016). We have previously shown that this guide does not influence neutrophilic inflammation in the zebrafish (Evans et al, 2019; Isles et al, 2019).…”
Section: Methodsmentioning
confidence: 99%